2014
DOI: 10.1002/adfm.201303766
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Energy Li‐Ion Battery Using a Silicon‐Based Anode and a Nano‐Structured Layered Composite Cathode

Abstract: High capacity electrodes based on a Si composite anode and a layered composite oxide cathode, Ni‐rich Li[Ni0.75Co0.1Mn0.15]O2, are evaluated and combined to fabricate a high energy lithium ion battery. The Si composite anode, Si/C‐IWGS (internally wired with graphene sheets), is prepared by a scalable sol–gel process. The Si/C‐IWGS anode delivers a high capacity of >800 mAh g−1 with an excellent cycling stability of up to 200 cycles, mainly due to the small amount of graphene (∼6 wt%). The cathode (Li[Ni0.75Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 51 publications
(62 reference statements)
2
102
0
Order By: Relevance
“…K. Sun et al [ 393 ] also reported a full-cell comprising a Nirich Li[Ni 0.75 Co 0.1 Mn 0.15 ]O 2 cathode and a pre-lithiated RGO/ Si hybrid anode (with a graphene content of about 6 wt%) ( Table 3 ). The cell, operating in the potential range 2.7-4.2 V, exhibited fi rst charge and discharge capacities of 206 and 196 mAh g −1 (at a current of 20 mA g −1 , based on the weight of cathode active material), respectively, yielding a Coulombic effi ciency of 95%.…”
Section: Full-cells Employing Graphene and Graphene-containing Anodesmentioning
confidence: 99%
“…K. Sun et al [ 393 ] also reported a full-cell comprising a Nirich Li[Ni 0.75 Co 0.1 Mn 0.15 ]O 2 cathode and a pre-lithiated RGO/ Si hybrid anode (with a graphene content of about 6 wt%) ( Table 3 ). The cell, operating in the potential range 2.7-4.2 V, exhibited fi rst charge and discharge capacities of 206 and 196 mAh g −1 (at a current of 20 mA g −1 , based on the weight of cathode active material), respectively, yielding a Coulombic effi ciency of 95%.…”
Section: Full-cells Employing Graphene and Graphene-containing Anodesmentioning
confidence: 99%
“…We present the effect of electrolyte composition, by adding various amounts of VC and FEC to our baseline electrolyte; such reports on electrolyte composition effects on silicon-containing full cells are still relatively few. 18,[21][22][23][24][25][26] We also describe the effect of voltage windows on cell performance and durability. We remind the reader that the effect of voltage windows on cell cycle life is intrinsically related to the negative and positive electrode's capacity matching (n:p ratio), and to the initial coulombic efficiency, which together dictate the electrode potential limits within a cell.…”
Section: -13mentioning
confidence: 99%
“…In spite of these efforts, the CEs achieved throughout cycling are still insufficient for a long-lasting Si-based full-cell 31,[33][34][35] or the methods employed to manufacture the full-cells introduce large excesses of Li þ (4200%) into the system that serve to counterbalance the cell efficiency losses over long-term cycling [36][37][38] . In the effort to design next-generation electrolyte materials, room temperature ionic liquids (RTILs or ILs) are of particular interest due to their low volatilities, negligible vapour pressures, thermal stabilities, high-voltage stability windows and sufficient ionic conductivities 39 .…”
mentioning
confidence: 99%